METODOLOGI PEMAHAMAN HADIS PERSPEKTIF YUSUF QARDAWI TENTANG HADIS KEWARISAN BEDA AGAMA - A. Fauzi Aziz; Wahidul Anam (Minhaj: Jurnal Ilmu Syariah, 2023)
There should be no ambiguity regarding how Islamic law interprets the concept of inheritance. This is so because both the Qur'an and the Sunnah provide comprehensive justifications for the inheritance law. With Hadyu al-Islam Fatwa Mu"sirah, Yusuf Qardawi has filled another linguistic gap regarding the legitimacy of Muslim inheritance from non-Muslims. This research employed library research as its research methodology. specifically by undertaking a documented analysis of the literature around the subject under investigation. The study's findings were then examined by making deductions that were deemed pertinent to serve as the foundation for the study's findings. The findings of this study demonstrate that there is room for interpretation when it comes to whether Muslims may inherit property from non-Muslims because, in Yusuf Qardawi's view, Islam does not obstruct or reject the right route that advances the interests of the people. Additionally, with inheritance or inheritance that can support upholding Allah's religion and obeying Him.